Consumer acceptance and willingness to pay for sago canton - Comendador, Neil Carla Y.
Sensory evaluation was done with 100 respondents who were invited to participate in the study through Group Interview technique. The respondents evaluated pancit canton, sago canton with malunggay (Moringa Oleifera) using the sensory evaluation forms given to them. Analysis of variance and Duncan Multiple Range Test were used to determine the degree of differences among the study components. Survey questionnaires were also provided to the respondents to gather informations about their socio-demographic status, willingness to pay for sago canton and additional willingness to pay for fair trade. Results show that sago canton varieties have visually unappealing color (brownish for the sago canton and greenish for sago canton with malunggay). The appearance, coupled with unfamiliar aroma affected the response of the respondents. However, between sago canton varieties, only the texture of sago canton was not preferred by the respondents over sago canton with malunggay. It was also observed that sago canton with malunggay has as aftertaste which was bitter to the mouth. This means that sago canton was more accepted by the respondents than of the sago canton with malunggay. Based on the results, 78 respondents were willing to pay for sago canton for 10.00-14.00 pesos. Majority of them were married females ranging 18 to 49 years old and have some college education. Moreover, 66 of them were willing to pay for additional 10%-15% for trade in sago canton.